Methods for environmental assessment of building materials - Eštoková, A. (Видавництво Національного університету «Львівська політехніка», 2007)
A building is an artificial environment designed and built to meet user need and material is the most basic product of building production. Building products so directly or indirectly interact with the environment. The main environmental evaluation methods as well as the simple example of environmental assessment of selected building material are presented in this paper.